Altered Expression of miR-518b and miR-519a in the Placenta is Associated with Low Fetal Birth Weight - Wang, Dan; Na, Quan; Song, Wei-Wei; Song, Gui-Yu (American Journal of Perinatology, 2014)
Objectives Previous studies have suggested that the expression and function of placenta-specific microRNAs (miRNAs) are associated with placenta trophoblastic proliferation and invasion. This study investigated whether the altered expression of placenta-specific miRNAs was involved in the development of fetal growth.Methods Placenta tissues were obtained from pregnant women with large for gestational age (LGA), intrauterine growth retardation (IUGR), and appropriate for gestational age (AGA) infants (n = 30 in each group). Real-time quantitative reverse transcription-polymerase chain reaction was used to analyze the expression of relative placenta-specific miRNAs in human placental tissues from three different groups.Results Compared with the LGA and healthy control (AGA) groups; the expression of miR-518b was decreased, whereas miR-519a was significantly increased in the placentas from the IUGR group (p < 0.05).Conclusion This study suggests that altered expression of placenta-specific miRNAs (miR-518b and miR-519a) may be involved in the development of IUGR.
Keywords: microRNAs; gene expression; placenta; real-time quantitative RT-PCR; intrauterine growth retardation; large for gestational age